2023
DOI: 10.3389/fcvm.2023.1157325
|View full text |Cite
|
Sign up to set email alerts
|

TCA cycle metabolites associated with adverse outcomes after acute coronary syndrome: mediating effect of renal function

Abstract: AimsTo examine relationships of tricarboxylic acid (TCA) cycle metabolites with risk of cardiovascular events and mortality after acute coronary syndrome (ACS), and evaluate the mediating role of renal function in these associations.MethodsThis is a prospective study performed among 309 ACS patients who were followed for a mean of 6.7 years. During this period 131 patients developed major adverse cardiovascular events (MACE), defined as the composite of myocardial infarction, hospitalization for heart failure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…An independent association of plasma citrate with CV mortality has been reported in two large-scale prospective studies [13,14]. Another prospective study examined the associations between TCA cycle components, including citrate, and the risk of developing CV events and mortality after an acute coronary syndrome [26]. This study in highrisk individuals identified positive associations of CV outcome with isocitrate, aconitate, isocitrate, d/l-2-hydroxyglutarate and adverse outcomes but not with citrate.…”
Section: Discussionmentioning
confidence: 81%
“…An independent association of plasma citrate with CV mortality has been reported in two large-scale prospective studies [13,14]. Another prospective study examined the associations between TCA cycle components, including citrate, and the risk of developing CV events and mortality after an acute coronary syndrome [26]. This study in highrisk individuals identified positive associations of CV outcome with isocitrate, aconitate, isocitrate, d/l-2-hydroxyglutarate and adverse outcomes but not with citrate.…”
Section: Discussionmentioning
confidence: 81%
“…Disturbances of TCA cycle can cause mitochondrial dysfunction, resulting in oxidative stress and a pro-inflammatory state 28 . Previous study revealed that elevated levels of plasma isocitrate, a component of TCA cycle, were associated with a higher risk of cardiovascular events in patients with acute coronary syndrome (a subtype of CAD) 29 . The elevated levels of isocitrate indicated the inactivity of mitochondrial NADP+-isocitrate dehydrogenase, which was an enzyme responsible for the oxidative decarboxylation of isocitrate 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients who suffered a non-type 1 myocardial infarction were further excluded. A detailed explanation of the definition of ACS can be found elsewhere [3,6]. After excluding those patients who did not have blood samples (n = 31), a total of 309 participants remained in the analysis (Supplementary Materials Figure S1) [14].…”
Section: Study Design and Populationmentioning
confidence: 99%
“…For instance, in patients with ACS, serum N-acetylneuraminic has been related to myocardial injury and the degree of coronary lesions, resulting in the possibility to use it as a biomarker for ACS patient risk assessment [5]. Other studies have reported associations of plasma tricarboxylic acid (TCA) cycle metabolites and plasma trimethylamine-N-oxide (TMAO) and its precursors with the risk of cardiovascular events in ACS patients [3,6]. Recently, gut microbiota-derived metabolites have attracted considerable attention for cardiovascular health [7,8].…”
Section: Introductionmentioning
confidence: 99%